Transmission of Earthquake Early Warning Message through a Different Channel: Karliova Case Study - Eren, Mehmet (GEOLOGICAL SOC INDIA, 2025)
Although we do not yet have the technological equipment to predict the location, time and magnitude of an earthquake, the Earthquake Early Warning (EEW) system can prevent the loss of life and property caused by earthquakes. In this study, it is aimed to explain the potential of using a different voice warning channel that will convey the message of EEW to the masses and has not been used anywhere before. In this context, it is proposed to integrate a network that can transmit voice messages from 89,817 points spread across T & uuml;rkiye (almost throughout the country) into the EEW system. The 24 January 2020 Elazig and 6 February 2023 Kahramanmaras earthquake sequences caused stress accumulation at the intersection of the North Anatolian Fault (NAF) and the East Anatolian Fault (EAF) zone. Since a large magnitude (MW>7) earthquake is expected in the Yedisu and Karl & yacute;ova region of Bing & ouml;l area, a simulated earthquake epicenter has been selected in this region. The proposed EEW will solve the earthquake parameters with the help of acceleration records from the seismograph network operated by the Disaster and Emergency Management Authority (AFAD). The obtained data will be calculated in the data processing center of AFAD and based on the earthquake magnitude, public buildings (mufti's offices) in the districts likely to be affected by the earthquake will be identified with the help of Geographic Information Systems (GIS). The warning message will be conveyed to the mufti's offices located in the district centers and will be announced aloud throughout the district, including the villages. The proposed system will increase the success of the system by preventing disruptions due to power outages by supporting the system with SMS messages. Thus, a unique EEW system potential will be demonstrated in warning the people living in these regions that may be affected by earthquakes.
Keywords: Public Safety; earthquake; EEW; P wave; GIS; Mufti's office; voice warning message; WAVE-FORMS; MAGNITUDE; SYSTEMS; Geology